2022
DOI: 10.3389/fnut.2022.821016
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Promote Healthy Eating Among University Students: A Qualitative Study Using the Nominal Group Technique

Abstract: IntroductionThe years spent at university are critical in terms of altering people's dietary patterns. This study aimed to: (1) understand the main dietary changes that students experience after starting university; (2) determine the personal and objective factors that hinder healthy eating, and (3) define possible strategies to facilitate healthier diets among university students.MethodsThe nominal group technique (NGT) was used to elicit ideas from 39 students from the University of Parma, Italy. The sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
1
10
1
2
Order By: Relevance
“…Our food choice findings also align with previous studies' results that attach importance to the taste factor (Sogari et al 2018;Ozturk and Akoglu 2020;Rajini et al 2021). Wongprawmas et al (2022) mentioned that being economical is important when choosing food for freshmen students. Garai-Fodor (2021) also stated that freshness, money, good taste, and smell were the most important factors in food choice for the Z generation, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Our food choice findings also align with previous studies' results that attach importance to the taste factor (Sogari et al 2018;Ozturk and Akoglu 2020;Rajini et al 2021). Wongprawmas et al (2022) mentioned that being economical is important when choosing food for freshmen students. Garai-Fodor (2021) also stated that freshness, money, good taste, and smell were the most important factors in food choice for the Z generation, respectively.…”
Section: Resultssupporting
confidence: 91%
“…In contrast to this, students discussed discount schemes and food vouchers for supermarkets to be bene cial in promoting healthy eating as they were able to purchase fresh produce whilst encouraging food preparation skills. Self-catering facilities on campus including microwaves, toasters, and communal spaces would also promote healthy cooking 45 . Free fruits and outlets offering fruits and vegetables on campus were identi ed as an ideal option to encourage healthy snacking, especially during university events where unhealthy food would otherwise be promoted 41,42,46 .…”
Section: Discussionmentioning
confidence: 99%
“…At the personal level, lack of willpower emerged as a key barrier, while being motivated and having the resolve to exercise or not eat sweet or calorie-rich food, despite the challenges, was identified as a facilitator. Willpower, defined as the capacity to exert self-control, has emerged in several studies as a barrier to healthy eating [ 32 , 33 ] and physical activity [ 34 ]. In Tsukayama et al’s [ 35 ] prospective longitudinal study, the researchers found that more self-controlled children were less likely to become overweight as they entered adolescence.…”
Section: Discussionmentioning
confidence: 99%